Kontribusi Private Investment Dan Belanja Modal Pemerintah Terhadap Nilai Tambah Ekonomi Dan Penyerapan Tenaga Kerja Kab/Kota Hight Economic Di Provinsi Jawa Timur (Kota Surabaya, Kota Kediri, Kab.Sidoarjo, Kab.Gresik) - Fatihudin, Didin (UNIVERSITAS NEGERI SURABAYA, 2012)
AbstractThe accumulation of capital in one of the determinants of economic growth factors in addition to the economic potential and population. Private investment and government capital expenditure is the implementation of capital accumulation then spent again to enlarge the production capacity and increase asset value. This study gives an overview of how the contribution of private investment and government capital expenditure of district/city economic hight on economic value added and employment in the province of East Java. District/city Surabaya, Kediri, Sidoarjo and Gresik selected from 38 districts/cities in East Java Province. The method of research used samples expost Pacto and purposive sampling techniques. Data obtained from the Central Bureau of Statistics, the Investment Coordinating Board and the Finance Bureau of East Java Governor's Office for five years from 2002 to 2006. Data processing is done manually assisted with Excel and SPSS software program. The results showed that the change in private investment and government capital spending districts / cities have contributed to the change in economic value added and the employment / town in East Java. Private investment and government capital expenditure is very important to increase economic activities in the region. Economic growth districts / cities that use capital-intensive approach (capital intensive) will not be able to absorb labor and expansion of new jobs as experienced Kediri, unless economic growth with labor-intensive approaches (labor intensive).